Fine-tuning of mononuclear phagocytes for improved inflammatory responses: role of soybean-derived immunomodulatory compounds - Tezuka, Hiroyuki; Imai, Shinjiro (Frontiers in Nutrition, 2024)
The concept of inflammation encompasses beneficial and detrimental aspects, which are referred to as infectious and sterile inflammations, respectively. Infectious inflammation plays a crucial role in host defense, whereas sterile inflammation encompasses allergic, autoimmune, and lifestyle-related diseases, leading to detrimental effects. Dendritic cells and macrophages, both of which are representative mononuclear phagocytes (MNPs), are essential for initiating immune responses, suggesting that the regulation of MNPs limits excessive inflammation. In this context, dietary components with immunomodulatory properties have been identified. Among them, soybean-derived compounds, including isoflavones, saponins, flavonoids and bioactive peptides, act directly on MNPs to fine-tune immune responses. Notably, some soybean-derived compounds have demonstrated the ability to alleviate the symptom of allergy and autoimmunity in mouse models. In this review, we introduce and summarize the roles of soybean-derived compounds on MNP-mediated inflammatory responses. Understanding the mechanism by which soybean-derived molecules regulate MNPs could provide valuable insights for designing safe immunomodulators.